Jenis Pertanyaan dan Gaya Bertanya Pembelajar dalam Korelasi Pembelajaran Bahasa Indonesia bagi Penutur Asing (BIPA) di Kelas - Dzakiyah Mega Wangi; Fahira Adind; Iren Christin Ferbina Ginting; Safinatul Hasanah Harahap (Departement of Mathematics Education, 2024)
This research aims to explain the types of questions and questioning styles used by BIPA students with their students. The type and style of questioning used by BIPA students can build communicative interactions between students and students in the classroom. This research uses a qualitative design based on two considerations. First, this research is inductive in nature which concludes the final results based on the data obtained. Second, this research is descriptive in nature with an effort to describe data and theory accurately and systematically. The data source in this research are 6th semester students of the Indonesian Language and Literature Education Study Program, Medan State University who are taking the Indonesian Language for Foreign Speakers (BIPA) course. The research focus contains data from a series of meetings to facilitate interpretation of the relationship between the types of questions and questioning styles used by BIPA students. Verbal data in the form of questions obtained from BIPA students was transcribed and arranged according to indicators of question type and style. The results of this research provide an overview of the types and styles of students' questions that are not limited to communication purposes only, but rather questions that help students stay focused on the learning objectives. The questions asked by students must be very well prepared and designed according to the students' BIPA level.